2023
DOI: 10.20452/pamw.16432
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of treatment response to serotonin and noradrenaline reuptake inhibitors in fibromyalgia

Abstract: What is new?Fibromyalgia (FM) patients are heterogenous in metabolic status. Contrary to the previously published data our study shows that only a subgroup of FM patients is characterized by insulin resistance. FM patients who are responsive to SNRI (serotonin and noradrenalin reuptake inhibitors) treatment have similar levels of fasting glucose, insulin, insulin resistance, BMI compared to healthy controls. However, FM patients who are not responsive to treatment with SNRI are characterized by higher fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Discrimination between these conditions is difficult, and treating them individually is inconvenient owing to the low efficacy of this approach [ 8 ]. Although TCAs and SNRIs are the first-line treatment options for this comorbid condition [ 9 , 15 , 17 ], they have been shown to be ineffective in a significant number of patients [ 10 , 13 , 19 ]. As there is little evidence that SSRIs are useful in CP [ 21 ], new treatment alternatives are needed for this comorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrimination between these conditions is difficult, and treating them individually is inconvenient owing to the low efficacy of this approach [ 8 ]. Although TCAs and SNRIs are the first-line treatment options for this comorbid condition [ 9 , 15 , 17 ], they have been shown to be ineffective in a significant number of patients [ 10 , 13 , 19 ]. As there is little evidence that SSRIs are useful in CP [ 21 ], new treatment alternatives are needed for this comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the presence of pain reduces the chance of recovery from depression and is related to more intense symptoms in these patients [ 8 ], including impaired sleep, enhanced anxiety, and impaired cognition [ 9 ]. Furthermore, in some cases, the presence of depression in patients with CP is a predictor of non-response to antidepressants [ 10 ]. Thus, this comorbidity exacerbates the symptoms of both conditions, making treatment more difficult and complicating the management of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we recently presented a pilot analysis exploring the links between IR and response to treatment with SNRI in MDD. The results indicated that MDD subjects resistant to SNRI were characterized by higher IR and BMI than those responsive to SNRI [28]. On the other hand, trials exploring the effectiveness of psychotherapy in adolescent girls with depression at risk of TMD2 failed to show the link between improvement of depression and IR [29].…”
Section: Antidepressant Treatment Efficacymentioning
confidence: 99%
“…In a study of fibromyalgia patients, of which 58% were comorbid with MDD, we found that IR, depression, anxiety and personality disorders were predictors of nonresponse to serotonin and noradrenaline reuptake inhibitors. Of interest, while subjects resistant to SNRI had significantly higher BMI than those responsive to SNRI, the relationship between BMI and resistance to SNRI was fully mediated by IR [ 27 ▪ ]. Also, we recently presented a pilot analysis exploring the links between IR and response to treatment with SNRI in MDD.…”
Section: Antidepressant Treatment Efficacymentioning
confidence: 99%